Detection of Bordetella pertussis by rapid-cycle PCR and colorimetric microwell hybridization. - Buck, G E (1996)
The use of rapid-cycle PCR combined with colorimetric microwell hybridization for detecting Bordetella pertussis was investigated. Rapid cycling was performed with an air thermocycler (model 1605; Idaho Technology, Idaho Falls, Idaho). Although the instrument was originally designed to be used with capillary tubes, an adapter that allows this instrument to be used with PCR tubes has recently been introduced. Because of the low heat capacity of air, the thermocycler has rapid transition rates between temperatures. The combination of a rapid temperature transition rate, small sample volume (10 microliters), and overshooting or undershooting of the temperature set points allowed the cycles to be reduced to 5 s for denaturation and 10 s for extension and annealing. Thus, the amplification could be completed in a total of approximately 35 min. Amplified DNA was detected with biotin-labeled primers and by hybridization to a capture probe immobilized in microwell plates. When simulated clinical specimens consisting of pooled nasopharyngeal washes with known numbers of B. pertussis organisms were examined by this procedure, as little as one organism per 5 microliters of sample could be detected. Six nasopharyngeal aspirates or washes from culture-positive patients were positive by PCR, as were two of seven specimens obtained from patients that were negative by culture and direct fluorescent-antibody assay. The two patients who were PCR positive but culture and direct fluorescent-antibody assay negative had clinical disease compatible with pertussis. This method appears to be a sensitive, convenient means of detecting B. pertussis in clinical specimens. The total time required for specimen processing, amplification, and detection is about 2.5 h.